Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Muslim Terhadap Produk Kosmetik - Ripah Saripah; Biki Zulfikri Rahmat; Qiny Shonia Az Zahra (eCo-Buss, 2023)
The cosmetics market in Indonesia is vast and will continue to grow every year. The large selection of local and foreign cosmetic brands in Indonesia causes customers to increasingly consider buying decisions. The purpose of this study was to determine the effect of sales promotion, brand image, and halal labeling on cosmetic purchasing decisions for Muslim consumers partially or simultaneously. The population in this study is unknown, the sample in this study used purposive sampling, namely cosmetic users as many as 100 respondents. The data collection technique is a questionnaire with a Likert scale. The data analysis technique is the correlation coefficient, regression coefficient and determination. The results of the study were obtained: 1) There is an effect of sales promotion on purchasing decisions by 28.6%. 2). there is an influence of brand image on purchasing decisions by 36.2% 3) there is an influence of the halal label on purchasing decisions by 37.1%. and 4) There is an influence between sales promotion, brand image and halal labeling on purchasing decisions by 45%. So it can be concluded that sales promotion, brand image, and halal labeling have a positive and significant effect on cosmetic purchasing decisions for Muslim consumers both partially and independently.